Komunikasi Bahasa Pada Masyarakat Desa Karangmulya Kecamatan Bojongmangu - Siti Nur Istikomah; Sinta Rosalina (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this researchdescribe communication stylePublic KarangMulya Village and understand what obstacles the local community experiences in communicating. This study uses a qualitative approach and analytical descriptive method. Data collection techniques using observation, interviews, documentation, and literature studies. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of the analysis show that the people of KarangMulya Village have a majority population who use Sundanese in their communication activities. Communication barriers experienced by the elderly community. This is because there is a lack of hearing so that it is difficult to interact.